SISTEM PENGAMBILAN KEPUTUSAN KREDIT PADA PT PEGADAIAN (PERSERO) CABANG PELITA MAKASSAR - Ahmad Firdaus; Adi Siswanto; Abdul Wahab (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
The purpose of this study was to determine the decision-making system for multipurpose credit creation at PT Pegadaian (Persero) Pelita Makassar Branch. The type of research used is descriptive qualitative where the author describes the results of observations and analyzes the data obtained in the field. Research conducted at PT Pegadaian (Persero) Pelita Makassar Branch from April to July 2021. The type of research used is descriptive qualitative, namely the author describes the results of observations and direct interviews. After conducting research and analyzing the discussion, it was found that: 1) The results showed that the credit decision-making system at PT Pegadaian (Persero) Pelita Makassar branch, namely creative credit consisted of a multipurpose creation credit decision-making mechanism divided into a credit limit of IDR 1,000,000.00 up to IDR 10,000,000.00 flat interest rate is 1.25% per month while the credit limit is IDR 10.100.000,00 up to IDR 50,000,000.00 flat interest rate of 1.15% per month and the decision maker is a micro analysis; 1) The mechanism for making credit decisions for multipurpose creations with a credit limit of IDR 50.100.000,00 up to IDR 100,000,000.00 flat interest rate is 1.05% per month and the decision maker is Asmen micro; 3) The purpose of granting multiguan creative credit is to assist individual customer businesses that require funds as working capital so that debtors can develop and expand their business.